China's Sex Ratio and Crime: Behavioral Change or Financial Necessity? - Lisa A. Cameron; Xin Meng; Dandan Zhang (Institute for the Study of Labor (IZA), 2016)
This paper uses survey and experimental data from prison inmates and comparable non-inmates to examine the drivers of rising criminality in China. Consistent with socio-biological research on other species, we find that China's high sex-ratios are associated with greater risk-taking and impatience amongst males. These underlying behavioral impacts explain some part of the increase in criminality. The primary avenue through which the sex-ratio increases crime, however, is the direct pressure on men to appear financially attractive in order to find a partner in the marriage market. These marriage market pressures result in a higher propensity to commit financially rewarding crimes.
Keywords: O12; J12; 330; crime; marriage markets; risk-taking; time preferences; sex-ratio; one child policy; China